Probing keto–enol tautomerism using photoelectron spectroscopy1. Issue 30 (14th August 2015) - Capron, Nathalie; Casier, Bastien; Sisourat, Nicolas; Piancastelli, Maria Novella; Simon, Marc; Carniato, Stéphane
<x xml:space="preserve">Abstract</x> We theoretically investigate the mechanism of tautomerism in the gas-phase acetylacetone molecule.